2020
DOI: 10.15190/d.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing for Prevention and Treatment of COVID-19: A Clinical Landscape

Abstract: SARS-CoV-2, the novel coronavirus strain responsible for the current pandemic of COVID-19, has rendered the entire humanity suffering. Several months have passed since the pandemic has struck. However, the world is still looking for an effective treatment plan to battle the viral infection. The first vaccine just received emergency approval in December 2020 for use in USA and UK. These are excellent news, however, the worldwide distribution of such vaccine, the possibility of virus mutation and the lack of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…Analysis of 198 high-quality complete genome of SARS-CoV-2 from Bangladesh revealed that the circulating strains are of many sub-lineages harboring the same ancestry as Wuhan virus, although their direct evolution from the reference Wuhan virus was not found. Two previous reports by Parvez et al [ 30 ] and Hasan et al [ 31 ] were consistent with our findings that the contributory strains in the SARS-CoV-2 outbreak in Bangladesh might be arising from the different regions of the world other than China. Besides, that majority of the Bangladeshi isolates were found to fall within the clade B belonging to L type (Supplementary Table ST2).…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of 198 high-quality complete genome of SARS-CoV-2 from Bangladesh revealed that the circulating strains are of many sub-lineages harboring the same ancestry as Wuhan virus, although their direct evolution from the reference Wuhan virus was not found. Two previous reports by Parvez et al [ 30 ] and Hasan et al [ 31 ] were consistent with our findings that the contributory strains in the SARS-CoV-2 outbreak in Bangladesh might be arising from the different regions of the world other than China. Besides, that majority of the Bangladeshi isolates were found to fall within the clade B belonging to L type (Supplementary Table ST2).…”
Section: Discussionsupporting
confidence: 94%
“…Other authors have reported cases of acute invasive fungal rhino-orbital mucormycosis 15 and cavitary pulmonary mucormycosis 5,16 in patients with COVID-19. Patients hospitalized for COVID-19 are at risk for healthcare-associated infections 17 , including candidemia, or bloodstream infections caused by Candida and other fungal diseases.…”
Section: Fungal Co-infections In Covid-19mentioning
confidence: 99%
“…Social distancing might be necessary to contain these deadly pathogens, but it comes with panic and socio-economic collapse [33]. However, considering vaccination, pandemic control measures and re-emergence of new variants, the global economic activity might reduce to 4% in 2021 and 3.8% in 2022 or to the darker side, might face downfall with below potential growth by 2022 if the situation getting worsen [34,35]. Besides, due to lockdown and other restrictions, mental health would wither away mainly because of unemployment which may also lead to crime, burglary, fraud business.…”
Section: 2possible Social Complications Of These Outbreaks In Near Futurementioning
confidence: 99%
“…Affording medical care would be difficult for low-income people, while avian influenza outbreak would cull domestic birds and disrupt the food supply chain (Figure 2). So, the mortality and morbidity rate would increase not only due to diseases but also due to malnutrition-associated complexities [34,35]. The World would face severe poverty, which is also currently evident with the COVID-19 outbreak [36].…”
Section: 2possible Social Complications Of These Outbreaks In Near Futurementioning
confidence: 99%